The Decline of the Cloth Industry in Birnbaum (Międzychód) After the Napoleonic Wars - Lorenz, Torsten (Studia Historiae Oeconomicae, 2018)
The Decline of the Cloth Industry in Birnbaum (Międzychód) After the Napoleonic Wars.